Crotalaria juncea L: Fiber Crops for Green Manure and Biological Control for Nematode - DJAJADI, . (Perspektif, 2011)
Most of Indonesian agricultural land has very low (less than 1% C) soil organic matter content which is unsuitable to support sustainability agricultural system.  As a fiber crop, Crotalaria juncea (sun hemp) possesses many characteristics of a green manure, growing vigorously to provide good ground coverage, performing symbiosis with rhizobium to fix nitrogen, and being a source of organic matter.  Incorporation green biomass of sun hemp with soil in soil tillage, contributed to soil N content of 52.7 kg N/ha and increased cane yield of 61 tones/ha at one year planting time.  In agricultural soil dominated by sand particle (86% sand content), addition of 1.6% C juncea mixed with 10% clay soil, has improved soil physical characteristic (increasing of aggregate stability, declining bulk density, and increasing soil water content), soil chemical characteristics (increasing soil N, P and C organic), and soil biological characteristics (increasing population of bacteria and fungi).  Furthermore, sun hemp can suppress population of parasitic soil nematode. The using of sun hemp as a green manure might be an essential component of sustainability agriculture system.Key words: C juncea, green manure, nematode, soil fertility, sustainability agriculture.